2015
DOI: 10.1080/01635581.2015.990575
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Paste Alters NF-κB and Cancer-Related mRNA Expression in Prostate Cancer Cells, Xenografts, and Xenograft Microenvironment

Abstract: Tomatoes may protect against prostate cancer development, possibly through targeting signaling pathways such as nuclear factor-κB (NF-κB). We investigated whether tomato paste could modulate NF-κB activity and cancer-related gene expression in human derived prostate cancer cells (PC3) and PC3 xenografts. PC3-cells were stably transduced with an NF-κB-luciferase construct, and treated with tomato extracts or vehicle control. Nude mice bearing PC3 xenografts were fed a Western-like diet with or without 10% tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…xenografts fed on a Western-like diet with 10% tomato paste for 6.5 weeks reported an inhibition of NF-κB activity, lycopene accumulation in the xenografts, and modulation of cancer and immune related genes [74]. Therefore, lycopene intervention studies of cancer patients should aim for raising the plasma lycopene levels above 1 µM and nutritionists should be looking into ways of increasing the bioavailability of lycopene from food/supplements so that plasma levels can be easily raised above 1.25µM.…”
Section: Discussionmentioning
confidence: 98%
“…xenografts fed on a Western-like diet with 10% tomato paste for 6.5 weeks reported an inhibition of NF-κB activity, lycopene accumulation in the xenografts, and modulation of cancer and immune related genes [74]. Therefore, lycopene intervention studies of cancer patients should aim for raising the plasma lycopene levels above 1 µM and nutritionists should be looking into ways of increasing the bioavailability of lycopene from food/supplements so that plasma levels can be easily raised above 1.25µM.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, they raise interest because of their wide use and their amount of healthy compounds. So far, most studies analyzing tomatoes as a food with potential anticancer properties focused on the activity of their single antioxidant compounds, such as lycopene, β‐carotene, etc, whereas few studies, especially epidemiological, analyzed them in their entirety (Askari, Parizi, Jessri, & Rashidkhani, ; Giovannucci, ; Kolberg et al, ; La Vecchia, ; Ramos‐Bueno, Romero‐Gonzalez, Gonzalez‐Fernandez, & Guil‐Guerrero, ). A higher consumption of tomatoes is compatible with current general recommendations aimed at increasing the intake of fruits and vegetables, because of fairly consistent epidemiological evidences that people consuming a diet rich in fruits and vegetables have a lower risk of developing various cancer types (World Cancer Research Fund/American Istitute for Cancer Research, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the anticancer activities of vitamin A are mainly associated with their antioxidant activities [72,73], other mechanisms have been proposed [74][75][76]. An animal study showed that dietary tomato and lycopene intake reduced the expression of genes involved in androgen metabolism/signaling pathways (Srd5a1, Srd5a2, Pxn, and Srebf1) in transgenic adenocarcinoma of the mouse prostate (TRAMP) mice [76].…”
Section: Vitamin Amentioning
confidence: 99%